Molecular differentiation of Angiostrongylus taxa (Nematoda: Angiostrongylidae) by cytochrome c oxidase subunit I (COI) gene sequences - Eamsobhana, Praphathip; Lim, Phaik Eem; Solano, Gabriela; Zhang, Hongman; Gan, Xiao Xian; Yong, Hoi Sen (Elsevier, 2010)
Nematodes of the genus Angiostrongylus are parasites of rodents and carnivores. They reside in the pulmonary or mesenteric arteries of their hosts. Two species are pathogenic in humans - Angiostrongylus cantonensis causes eosinophilic meningitis or meningoencephalitis, and Angiostrongylus costaricensis produces abdominal angiostrongyliasis. In addition Angiostrongylus malaysiensis may have the potential of being pathogenic in humans. The mitochondrial gene cytochrome c oxidase subunit I (COI) of these Angiostrongylus species and three geographical isolates (China, Hawaii and Thailand) of A. cantonensis were studied by polymerase chain reaction amplification and DNA sequencing. COI sequences of A. cantonensis, A. costaricensis and Angiostrongylus vasorum in the GenBank were included for comparison. Phylogenetic analysis by maximum-likelihood (ML), maximum-parsimony (MP), neighbour-joining (NJ) and Bayesian inference (BI) produced similar tree topology except variation in the bootstrap support values. There were two major clades - (1)A. cantonensis and A. malaysiensis, and (2) A. costaricensis and A. vasorum. The three geographical isolates of A. cantonensis formed a clade with low to high bootstrap values, and consisted of two subclades: (a) China and Hawaii isolates, and (b) monophyletic Thailand isolate. The individuals of each isolate formed a distinct cluster. In the second major clade, the Europe isolates of A. vasorum were distinctly different from the Brazil isolates. For A. costaricensis, the Costa Rica isolate was distinct from the Brazil isolate with an uncorrected (p) distance of 11.39%, indicating the possible occurrence of cryptic species. The present results indicate that COI sequences might be a useful marker for differentiating geographical isolates of A. cantonensis and in uncovering cryptic species. Efforts are being made to carry out an extensive collaborative study to cover a wide range of Angiostrongylus species and geographical isolates.